Postmastectomy RT decision for lymph node negative patients: Turkish radiation oncology society - Altınok, Ayşe; Gürsel, Bilge; Ergen, A.; Alanyalı, Senem; Özsaran, Zeynep; Ay, Ahmet; Metcalfe, Evrim; Akmansu, Müge; Tepetam, Hüseyin; Altınok, Pelin; Altmışdörtoğlu, Özgür; Serarslan, Alparslan; et al. (Elsevier Ireland Ltd, 2018)
Early Breast Cancer Trialists’ Collaborative Group meta analyses have shown that postmastectomy radiotherapy (PMRT) had no significant effect on locoregional recurrence (LRR), overall recurrence or breast cancer mortality for patients without lymph node metastases. On the other hand it has also been shown that the risk of developing LRR is rising up to 15% or more for women in the presence of two or more adverse factors even though there is no lymph node involvement. In this study, PMRT indications were evaluated in 12 centers, overall Turkey to observe and document the decision making after mastectomy.
37th Meeting of the European-Society-for-Radiotherapy-and-Oncology (ESTRO) -- APR 20-24, 2018 -- Barcelona, SPAIN
WOS: 000438676100060